Sofijska polonistyka i współczesne bułgarskie polonofilstwo - Rikew, Kamen (Postscriptum Polonistyczne, 2020)
The paper gives an overview of the history and presentday status of Polish studies at St Kliment Ohridski University in Sofia and discusses several key aspects of Polish cultural presence in contemporary Bulgaria. It explains the specific structure of Polish philology studies at the University in the light of the country’s modern educational system and highlights the most prominent scholars that have shaped the prestige of this particular branch of Slavistics. Apart from academic research and educational achievements, another factor playing a significant role in presentday PolishBulgarian cultural dialogue is the Polish Institute in Sofia. The paper demonstrates how positive attitudes towards Poland and its cultural heritage have substantially influenced the reception of prominent Poles in Bulgaria. The cases of Lech Wałęsa, pope John Paul II and Czesław Miłosz reveal a tendency to idealize their legacy due to the need of public values lacking in Bulgarian society.